Study on the driving force of seasonal changes of soil erosion in Lulang-Tongmai section of Sichuan-Tibet Highway - Xu Tong; Zhu Kangcheng; Wu Hua; Chen Yingzhu; Zhou Jianwei; Chen Linna; Kong Yuzhong (PLoS ONE, 2025)
In the context of global climate change, the section of the Sichuan-Tibet Highway from Lulang to Tongmai has become a focal point for soil erosion research due to its unique geographical location and complex natural environment. Studies have shown that between 2000 and 2023, soil erosion intensity in this area has decreased. However, erosion intensity increases from southwest to northeast, with particularly severe erosion near the Tongmai Grand Bridge and Polong Gou Grand Bridge. Correlation analysis reveals a significant positive correlation between rainfall and soil erosion, while vegetation cover is positively correlated with erosion in the short term but contributes to reduced erosion over the long term. Geodetector analysis indicates that the main driving factors vary by season. In spring, summer, and autumn, temperature and precipitation are the primary drivers, with driving forces of 0.78 and 0.75, 0.80 and 0.78, and 0.75 and 0.73, respectively. In winter, temperature and elevation are the dominant factors, with driving forces of 0.63 and 0.42. The interaction between temperature, precipitation, and other factors significantly influences soil erosion, particularly in spring and summer, where the interaction driving force exceeds 0.75. These findings provide both theoretical support and decision-making guidance for soil erosion control along the Sichuan-Tibet Highway.